Immobilized Lipase in the Synthesis of High Purity Medium Chain Diacylglycerols Using a Bubble Column Reactor: Characterization and Application - Chen, Jiazi; Lee, Wan Jun; Qiu, Chaoying; Wang, Shaolin; Li, Guanghui; Wang, Yong (Frontiers in Bioengineering and Biotechnology, 2020)
Novozym® 435, an immobilized lipase from Candida antarctica B. (CALB), was used as a biocatalyst for the synthesis of high purity medium chain diacylglycerol (MCD) in a bubble column reactor. In this work, the properties of the MCD produced were characterized followed by determining its practical application as an emulsifier in water-in-oil (W/O) emulsion. Two types of MCDs, namely, dicaprylin (C8-DAG) and dicaprin (C10-DAG), were prepared through enzymatic esterification using the following conditions: 5% Novozym® 435, 2.5% deionized water, 60°C for 30 min followed by purification. A single-step molecular distillation (MD) (100–140°C, 0.1 Pa, 300 rpm) was performed and comparison was made to that of a double-step purification with MD followed by silica gel column chromatography technique (MD + SGCC). Crude C8-DAG and C10-DAG with DAG concentration of 41% and 44%, respectively, were obtained via the immobilized enzyme catalyzing reaction. Post purification via MD, the concentrations of C8-DAG and C10-DAG were increased to 80% and 83%, respectively. Both MCDs had purity of 99% after the MD + SGCC purification step. Although Novozym® 435 is a non-specific lipase, higher ratios of 1,3-DAG to 1,2-DAG were acquired. Via MD, the ratios of 1,3-DAG to 1,2-DAG in C8-DAG and C10-DAG were 5.8:1 and 7.3:1, respectively. MCDs that were purified using MD + SGCC were found to contain 1,3-DAG to 1,2-DAG ratios of 8.8:1 and 9.8:1 in C8-DAG and C10-DAG, respectively. The crystallization and melting peaks were shifted to higher temperature regions as the purity of the MCD was increased. Dense needle-like crystals were observed in MCDs with high purity. Addition of 5% C8-DAG and C10-DAG as emulsifier together in the presence of 9% of hydrogenated soybean oil produced stable W/O emulsion with particle size of 18 μm and 10 μm, respectively.